Comparison of phytochemicals, antimicrobial, and antioxidant capacities in different anatomical parts of Ficus microcarpa (Moraceae). Issue 3 (26th January 2017) - Rjeibi, Ilhem; Ncib, Sana; Alimi, Hichem; Ben Saad, Anouar; Saïd, Imen; Souid, Sami
Abstract: The aim of the present study was to compare the nutritional value, chemical composition, antioxidant capacity, and antimicrobial activity of leaves, fruits, and roots from Ficus microcarpa . The results showed that all plant parts are rich sources of sulfated polysaccharides and phenolics; in aerial roots, polyphenols and flavonoids dominate. Epicatechin, coumaric acid, and quercetin were present in roots, leaves, and fruits, but in different amounts. Gallic acid and rutin were detected only in roots extracts. The minerals compositions indicated that K, Na, Mn, Fe, Cu, and Zn were present in all plant parts. The antioxidant properties determined by hydrogen peroxide scavenging assays and 2, 2‐diphenyl‐1‐picrylhydrazyl assays, and antimicrobial activity against Staphylococcus aureus, Micrococcus luteus, Escherichia coli, and Pseudomonas aeruginosa were better in root and in correlation with the chemical composition changes. Practical applications: Our results provided evidence that the F. microcarpa could be a potential source of natural antioxidant that may replace synthetic product and prevents from oxidative stress induced by reactive oxygen species. Moreover, due to its potential antimicrobial activity, F. microcarpa can be used in pharmaceutical industry to treat damages caused by some pathogenic germs.